Identification of Pentatricopeptide Repeat Proteins in the Model Organism Dictyostelium discoideum - Sam Manna; Jessica Brewster; Christian Barth (International Journal of Genomics)
Pentatricopeptide repeat (PPR) proteins are RNA binding proteins with functions in organelle RNA metabolism. They are found in all eukaryotes but have been most extensively studied in plants. We report on the identification of 12 PPR-encoding genes in the genome of the protist Dictyostelium discoideum, with potential homologs in other members of the same lineage and some predicted novel functions for the encoded gene products in protists. For one of the gene products, we show that it localizes to the mitochondria, and we also demonstrate that antisense inhibition of its expression leads to slower growth, a phenotype associated with mitochondrial dysfunction.